Próba budowy demoekonometrycznego modelu gospodarki Polski - Sojka, Elżbieta (Wydział Prawa i Administracji UAM, 1984)
The study presents a structural form of demoeeonometric model of Polish economy. Generally, demoeeonometric models are mathematical ones, which are coding relations existing between basic economic and demographic values in formalized way. They allow to examine mechanisms of interactions of economic and demographic factors and to establish whether changes in demography are determined by economic phenomena and vice versa. The described model is linear with the exception of equasion determining variables Y5, Y6. It consists of 58 variables, 39 out of which are endogenous. The endogenic sphere of a model is divided into 6 blocks i.e.: employment, GNI, investments, foreign trade, consumption and demographic phenomena. Dynamic series of the period of 1960-1981 (21 years) became a basis of model estimation. Demo econometric model of Polish economy will be used for ex-ante simulation and construction of variant prognoses. Having assumed defined sequences of describing variables for future periods, it would be possible to calculate expected values for endogenous variables representing basic economic and demographic phenomena and to find their paths of growth.
Attempt at construction of demo-econometric model of Polish economy